2000
DOI: 10.1006/viro.2000.0223
|View full text |Cite
|
Sign up to set email alerts
|

Precise Mapping of the Replication and Transcription Promoters of Human Parainfluenza Virus Type 3

Abstract: The terminal RNA regions of the genomic and antigenomic RNAs of the paramyxoviruses and rhabdoviruses are known to contain sequences essential for directing RNA replication and transcription. The 3' terminus (leader region) of the negative-sense, genomic RNA of the rhabdoviruses and paramyxoviruses is known as the leader (Le) promoter and directs synthesis of positive-sense replication and transcription products. The 3' terminus of the antigenome is termed the trailer complementary (TrC) promoter and directs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 33 publications
4
79
1
Order By: Relevance
“…Seven of the eight residues contained in nt 36 to 43 of the RSV Le are U, suggesting that this U-rich nature is an important feature. The finding that nucleotides at the end of Le are important for transcription is consistent with findings for VSV, SeV, and parainfluenza virus type 3 (4,20,27,39), suggesting that the sequences immediately upstream of the promoter-proximal GS signal are important for many mononegaviruses. However, it should be emphasized that although nt 36 to 43 increased the efficiency of initiation from the GS signal, this region was not required for correct initiation, synthesis of complete mRNA, or the initiation of stop-start sequential transcription.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Seven of the eight residues contained in nt 36 to 43 of the RSV Le are U, suggesting that this U-rich nature is an important feature. The finding that nucleotides at the end of Le are important for transcription is consistent with findings for VSV, SeV, and parainfluenza virus type 3 (4,20,27,39), suggesting that the sequences immediately upstream of the promoter-proximal GS signal are important for many mononegaviruses. However, it should be emphasized that although nt 36 to 43 increased the efficiency of initiation from the GS signal, this region was not required for correct initiation, synthesis of complete mRNA, or the initiation of stop-start sequential transcription.…”
Section: Discussionsupporting
confidence: 84%
“…In the case of VSV, it has been shown that a synthetic template containing 17 nt of wt sequence is a functional promoter in vitro (34), and the first 15 nt of wt sequence can act as a promoter in an intracellular minigenome assay (39). The first 12 nt of the genome and antigenome are conserved in all of the Paramyxovirinae, and these nucleotides have been shown to be critical for RNA replication in parainfluenza virus type 3 (20), suggesting that this is the typical size of the 3Ј-terminal element of the mononegavirus replication promoter. In the case of members of the Paramyxovirinae, the replication promoter contains a second essential cis-acting element located within the first gene (20,21,29,37), but this additional element is not present in RSV or VSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many paramyxoviruses, such as SV5, SeV, and human parainfluenza virus type 3, the genomic promoter contains two 18-base promoter elements (PrE) that are essential for viral RNA synthesis (19,43,31,32). PrE-I is located at the ultimate 3Ј end of the genome and is separated from a second internal PrE, PrE-II, by a sequence-independent spacer region ( Fig.…”
mentioning
confidence: 99%
“…In vivo HPIV3 minigenome assay was performed as described previously (Hoffman et al, 2000) with slight modifications. HeLa cell monolayers in 12 well plate, grown to 90% confluency, were infected with recombinant vaccinia virus vTF7-3, which expresses T7 RNA polymerase, at an MOI of 3.…”
Section: In Vivo Minigenome Assaymentioning
confidence: 99%